Wnt pathway in bone: knowledge structure and hot spots from 1993 to 2022 - Liu, Tun; Zhao, Jiaxin; Zhang, Xinyi; Wang, Yulin; Wang, Wei; Song, Jidong (Frontiers in Physiology, 2023)
The role of the Wnt pathway in bone and its targets in skeletal disease has garnered interest, but the field lacks a systematic analysis of research. This paper presents a bibliometric study of publications related to the Wnt signaling pathway in bone to describe the current state of study and predict future outlooks. Methods: All relevant articles and reviews from 1993 to 2022 were collected from the Web of Science Core Collection (WoSCC). Bibliometric analysis and visualization were performed using CiteSpace 6.1 R3, VOSviewer 1.6.15, and the Online Analysis Platform of Literature Metrology (http://bibliometric.com/). Results: A total of 7,184 papers were retrieved, authored by 28,443 researchers from 89 countries/regions and published in 261 academic journals. The annual publication numbers peaked in 2021. China and USA are the leading countries, with the University of California and Harvard University as the most active institutions. Wang, Yang is the most prolific author. Bone has the most published research, while Proceedings of the National Academy of Sciences of the United States of America is the most cited journal on average. The main keywords include expression, Wnt, osteoporosis, bone, and osteogenic differentiation. Current and developing research hotspots focus on bone mass, sclerostin antibody, multiple myeloma, and cartilage development. Conclusion: This paper provides new insights for researchers to delve into the mechanisms of Wnt and bone related diseases and translate into clinical studies. It reveals the development and future research trends in Wnt and skeletal-related studies.